Review article: post‐TIPSS hepatic encephalopathy—current knowledge and future perspectives. Issue 10 (18th February 2022) - Gairing, Simon Johannes; Müller, Lukas; Kloeckner, Roman; Galle, Peter R.; Labenz, Christian
Summary: Background: In light of the global rise in the burden of chronic liver diseases and liver cirrhosis, the number of patients suffering from decompensation events is expected to increase. Transjugular intrahepatic portosystemic shunts (TIPSS) provide effective long‐term symptom control and may prolong transplant‐free survival in portal hypertension‐driven recurrent ascites and variceal bleeding. New‐onset or recurrent hepatic encephalopathy (HE) after TIPSS insertion (post‐TIPSS HE) represents the most severe post‐interventional complication. Aims: To provide insight into the epidemiology and risk factors for post‐TIPSS HE and scrutinize the current state of the art in treatment and drug therapy options. Methods: We conducted a literature search on post‐TIPSS HE in patients with liver cirrhosis. Results: Post‐TIPSS HE occurs in up to 54.5% of cases and particularly early recurrent HE is associated with a dismal prognosis. In recent years, several risk factors for the development of post‐TIPSS HE have been identified. These include not only parameters reflecting liver function (model for end‐stage liver disease score/Child‐Pugh score) as well as cognitive dysfunction caused by minimal HE but also extrahepatic factors such as sarcopenia and common medications such as proton pump inhibitors. In addition, new data on the benefit of rifaximin and of smaller stent grafts emerged and may improve the prevention of post‐TIPSS HE. Conclusions: Careful selection of TIPSS candidates is of utmost importance to reduce the risk of post‐TIPSS HE. In this narrative review, we provide a concise overview of the current epidemiology and risk factors of the treatment options for post‐TIPSS HE. Abstract :